1인 미디어 창작자의 플랫폼 선택에 영향을 미치는 요인 연구 : 유튜브, 트위치, 아프리카TV를 중심으로 - 방은혜(Eun-Hye Bang); 김예림(Ye-Lim Kim); 나화승(Hwaseong Na); 이상우(Sang-Woo Lee) (한국콘텐츠학회 논문지, 22(7), 2022)
Although personal media have become a giant industry, there is a lack of understanding of personal media creators. Therefore, this study aims to clarify factors influencing personal media creators' choice of platform. According to the analysis, there is a significant difference between the factors considered by YouTube, AfreecaTV, and Twitch creators. Moreover, the moderating effect of creators' main genre and broadcasting type were also found to be partially significant. It was found that both creators who share the motive of vividness and communication as their main genre and creators who focus on recording and broadcasting with career development motivation prefer YouTube. 1인 미디어 창작활동은 경제적 가치를 창출하는 하나의 산업으로 자리매김하고 있지만, 창작자에 대한 이해는 미비한 실정이다. 본 연구에서는 1인 미디어 창작자가 활동 플랫폼을 선택할 때 고려하는 중요 요인들을 창작자의 동기와 플랫폼의 특성에 초점을 맞추어 분석하였다. 연구결과, 생생함과 경력개발, 알고리즘 기반 적합도를 중시하는 창작자는 유튜브를, 상호작용과 수익창출 동기를 중시하는 창작자는 아프리카TV를, 상호작용, 서비스품질, 네트워킹 기회제공을 고려하는 창작자들은 트위치를 선택할 가능성이 높은 것으로 나타났다. 창작자의 주력 장르와 방송유형 변수의 조절효과 역시 일부 유의한 것으로 확인되었다. 생생함의 동기를 중시하며 소통을 주력장르로 하는 창작자와 경력개발 동기를 가지고 녹화방송에 주력하는 창작자의 경우 모두 유튜브를 선호하는 것으로 나타났다. 본 연구는 1인 미디어 연구에 대한 기존 연구의 시각을 확장하였으며, 미디어 플랫폼의 향후 시장 내 위상 정립의 방향을 제시하였다는 점에 의의가 있다.